Effect of ZnO-water based nanofluids from sonochemical synthesis method on heat transfer in a circular flow passage. (May 2020) - Ahmed, Waqar; Chowdhury, Z.Z.; Kazi, S.N.; Johan, MR.; Akram, Naveed; Oon, C.S.
Abstract: Present research work highlighted the synthesis of ZnO Nanoparticles by sonochemical method and its positive effects on enhancement of heat transfer while used as water based nanofluids in a circular tube heat exchanger. ZnO nanoparticles were synthesized by using Zinc acetate (ZnC4 H6 O4 ) and Sodium Hydroxide (NaOH) as the raw materials. Proper formation of ZnO nanoparticles were confirmed by XRD, FTIR, FESEM, EDX mapping and UV–vis spectrum characterizations. ZnO nanoparticles were been dispersed in distilled water by uisng high probe sonication and its concentration was varied (0.1%, 0.075%, 0.05% and 0.025%) to study its effect on convective heat transfer (Nusselt number) with the variation of Reynolds number in single tube circular heat exchanger. Positive enhancement in thermal conductivity was observed with the addition of ZnO nanoparticles in the base fluid and studied its performance at 50 °C heat transfer surface temperature and 30 °C bulk temperature of the nanofluids. About 49% increase in Nusselt numbers was observed at 0.1% wt. concentration of ZnO-water based flowing Nano fluid. At the highest Reynolds number (Examined), there was about 50% heat transfer enhancement noticed at 0.1% concentration of ZnO nanofluid. While all other weight % concentrations also showed enhanced heat trasnfer properties as compare to base fluid. The ZnO with distilled water nanofluids gives encourging results for heat trnasfer improvments. Graphical abstract: Unlabelled Image Highlights: Preparation of Zinc oxide Nanoparticles by Sonochemical Synthesis. Characterizations of Zinc oxide Nanoparticles for confirmation of synthesis. Preparation of ZnO-DW based well dispersed and stable nanofluids by using probe sonication. Evaluation of Heat transfer and Thermos physical properties of ZnO-DW based nanofluids.